2020
DOI: 10.3390/medicina56060273
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Prediction Using SOFA Score in Critically Ill Surgical and Non-Surgical Patients: Which Parameter Is the Most Valuable?

Abstract: Background and Objectives: assessment systems, such as the Sequential Organ Failure Assessment (SOFA) scale, are routinely used in intensive care units (ICUs) worldwide in order to predict patients’ outcome. We aimed to investigate SOFA’s usefulness in the prognostication of ICU mortality, including an analysis of the importance of its variables. Materials and Method: this single-centre observational study covered 905 patients that were admitted from 01.01.2015 to 31.12.2017 to a tertiary mixed ICU. The SOFA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 11 publications
1
11
0
3
Order By: Relevance
“…To improve screening, it has been suggested to assess them concomitantly with some well-known markers of systemic inflammation, including leucocytosis, C-Reactive Protein (CRP) or procalcitonin (PCT) [ 10 , 11 ]. To improve prognostication, they could be used in addition to some well-known ICU scorings, including APACHE II (Acute Physiology and Chronic Health Evaluation II), SAPS II (Simplified Acute Physiology Score II) and SOFA (Sequential Organ Failure Assessment) [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…To improve screening, it has been suggested to assess them concomitantly with some well-known markers of systemic inflammation, including leucocytosis, C-Reactive Protein (CRP) or procalcitonin (PCT) [ 10 , 11 ]. To improve prognostication, they could be used in addition to some well-known ICU scorings, including APACHE II (Acute Physiology and Chronic Health Evaluation II), SAPS II (Simplified Acute Physiology Score II) and SOFA (Sequential Organ Failure Assessment) [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients followed in the ICU is a heterogeneous group with various complications and different clinical conditions, and it is known that the mortality rate of these patients is high. SOFA, one of the mortality estimation models used in the ICU, was first developed to determine the severity of organ dysfunction in septic patients, but later it was determined that it could also be an indicator of disease severity in critically ill patients in ICU, and it started to be used as a mortality indicator in recent years [14][15][16]. In our study, expectedly, the SOFA score was higher in the non-survivor group.…”
Section: Discussionmentioning
confidence: 51%
“…This study also found that the SOFA score and 72 hr fluid balance were independent risk factors for mortality in these patients. SOFA score is a reliable indicator to assess the severity of critical ill patients [22,23]. Its predictive value for the mortality of patients with sepsis has been confirmed by a large number of studies and would not be discussed further here [24,25].…”
Section: Discussionmentioning
confidence: 99%